Acute physiological responses to ultra short race-pace training in competitive swimmers - Williamson, D.; McCarthy, E.; Ditroilo, M. (Journal of Human Kinetics, 2020)
Ultra Short Race Pace training (USRPT) is an emerging training modality devised in 2011 to deviate from high-volume swimming training that is typically prescribed. USRPT aims to replicate the exact demands of racing, through its unique prescription of race-pace velocity sets with short rest intervals. It has been surmised, with little physiological evidence, that USRPT provides swimmers with the best opportunity to optimize the conditioning, technique, and psychology aspects of racing at the most specific velocity of the relevant event, with low blood lactate concentration. The aim of this study was to examine acute physiological responses of USRPT. Fourteen swimmers were recruited to perform a USRPT set: 20 x 25 m freestyle with a 35-s rest interval. Swimmers were required to maintain the velocity of their 100 m personal best time for each sprint. Sprint performance, blood lactate, heart rate and the RPE were measured. Blood lactate was taken before, during (after every 4 sprints) and 3 minutes after the USRPT protocol. Heart rate monitors were used to profile the heart rate. Athletes reported the RPE before- and after completion of the USRPT set. Sprint times increased by 3.3-10.8% when compared to the first sprint (p < 0.01). There was high blood lactate concentration (13.6 ± 3.1mmol/l), a significant change in the RPE from 8 ± 1.6 to 18 ± 1.6 (p < 0.01) and a substantially high heart rate profile with an average HRmax of 188 ± 9 BPM. The results show the maximal intensity nature of USRPT and portray it as an anaerobic style of training.